Blueprint : Easy Future Sdn. Bhd. “Safe Corner Book” / Siti Sakinah Zuhari - Zuhari, Siti Sakinah (2020)
Easy Future Sdn. Bhd. company offers a new product call the Safe Corner Book. Our product is very simple, user friendly and also very effective to be use for everyone. Besides from having reasonable and affordable price, the design and style of the product is very fresh and attractive. We are committed to offer wonderful design and good quality product to meet the consumer demands and requirements. Safe Corner Book is a protector for corner and side of book cover that can be used easily according to your suitability. The users can use the protector on any books whether textbooks, notebooks or novels that can be up to 60 cm of the book length. This Safe Corner Book will able to secure the corner and side of book cover. Besides that, it can also save time of the users as the design is protector attach with adjustable tape that convenience the users to wrap the side and corner of the book cover